Aseismic retrofitting of loess cave using composite materials by shaking table test. (15th July 2021) - Zhao, Xiangbi; Xue, Jianyang; Zhang, Fengliang; Liu, Xuhao; Luo, Zheng; Ma, Linlin; Zhang, Wei
Highlights: A set novel retrofitting with composite materials is proposed to enhance the seismic performance of existing damaged LC. Earthquake performance of retrofitted LC is studied by shaking table tests. The solution substantially improves stiffness, strength, and stability of LC under seismic action. The seismic capacity of retrofitted LC structure is improved significantly compared with un-retrofitted LC. Abstract: Many of the existing loess cave (LC) dwellings are seismically vulnerable and require retrofitting. This paper investigates the seismic performance of LC structure after seismic retrofitting using strengthening methods with composite materials of traditional (masonry) and modern (steel bar and sodium silicate). Based on LC specimen with a 1:5 scale destroyed by the simulated earthquake action, seismic performance of retrofitted LC structure with the retrofitting technology was studied. Two different effective strengthening methods were retrofitted to the shear failure area of arch apex at the upper two caves on an un-retrofitted LC specimen. The retrofitted LC specimen was subjected to a series of earthquake motions on shaking table tests. The experiment results demonstrated that with the increase of the peak ground acceleration, the natural frequency and stiffness of the retrofitted LC specimen decreased, and the damping ratio increased, and then the acceleration amplification factor of each layer was between 1.02 and 1.41. Compared with the test phenomenon before retrofitting, the position of the X-type shear crack at the top of the arch moved upper the reinforcement area (the location of the original shear crack). These retrofitting techniques with composite materials improved the seismic capacity of the retrofitted LC structure.